2015
DOI: 10.1371/journal.pone.0117594
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Four Methionine Sulfoxide Reductases in Staphylococcus aureus

Abstract: Staphylococcus aureus is a major human pathogen and emergence of antibiotic resistance in clinical staphylococcal isolates raises concerns about our ability to control these infections. Cell wall-active antibiotics cause elevated synthesis of methionine sulfoxide reductases (Msrs: MsrA1 and MsrB) in S. aureus. MsrA and MsrB enzymes reduce S-epimers and R-epimers of methionine sulfoxide, respectively, that are generated under oxidative stress. In the S. aureus chromosome, there are three msrA genes (msrA1, msrA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 53 publications
5
45
0
Order By: Relevance
“…This might be explained by the high concentrations of H 2 O 2 that we used for the survival assays in vitro. Other studies addressing the role of bacterial methioinine sulfoxide reductases in the oxidative stress response use similar or even higher concentrations of H 2 O 2 , which are presumably required because of the redundancy of methionine sulfoxide repairing enzymes (Denkel et al, 2011;Douglas et al, 2004;Lee et al, 2009;Singh & Singh, 2012;Zhao et al, 2010). Methionine is susceptible to oxidation in its free and protein-bound form (Weissbach et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the high concentrations of H 2 O 2 that we used for the survival assays in vitro. Other studies addressing the role of bacterial methioinine sulfoxide reductases in the oxidative stress response use similar or even higher concentrations of H 2 O 2 , which are presumably required because of the redundancy of methionine sulfoxide repairing enzymes (Denkel et al, 2011;Douglas et al, 2004;Lee et al, 2009;Singh & Singh, 2012;Zhao et al, 2010). Methionine is susceptible to oxidation in its free and protein-bound form (Weissbach et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…at 37 C for the duration of all growth experiments (Controlled Environment Incubator Shaker; New Brunswick Scientific). All samples from various S. aureus cultures were diluted by serial 10-fold dilutions and plated on Singh & Singh (2012) *S. aureus strains were suspended in TSB containing 10 % glycerol for long-term storage and kept at À70 C. Frozen cultures were thawed at room temperature. Fifty microlitres of each S. aureus strain was inoculated in 5 ml of TSB and incubated overnight (16-18 h) at 37 C.…”
Section: Methodsmentioning
confidence: 99%
“…The apparent lack of persister cells in early exponential phase may be due, in part, to low concentrations of persister proteins that may act as quorum-sensing molecules (Lewis, 2007). Others have shown that two processes may influence persister formation: a stochastic variation in the level of specific persister proteins and a controlled, regulated threshold level of these proteins which may be dependent on population density (Lewis, 2007;Tashiro et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of detoxifying ROS is demonstrated by the many mechanisms used by S. aureus that include scavenging and neutralizing ROS, such as O 2 2 and H 2 O 2 , with SODs (SodA and SodM) and catalase (KatA), respectively [37,38]. In addition, the iron-regulated surface-determinant proteins IsdA and IsdB have been implicated in increasing S. aureus resistance to killing by H 2 O 2 [21], as well as methionine sulfoxide reductases to reduce oxidized methionine residues following oxidative stress that increase S. aureus resistance to ROS [39]. Unlike previously described mechanisms to neutralize ROS, our data suggest that S. aureus can directly inhibit H 2 O 2 and HOCl production, resulting in increased S. aureus survival.…”
Section: Saer/s-regulated Factors Reduce the Production Of Neutrophilmentioning
confidence: 99%